Uma análise dos determinantes da balança comercial de serviços municipais de Fortaleza - Evangelista, Mônica Ciarlini Teixeira (2020)
This study considers the importance of municipal financial autonomy to investigate the determinants of the municipal services trade balance in the city of Fortaleza between 2015 and 2018. As a reference, the 3,286 brazilian municipalities with which the capital of Ceará interacts, exporting or importing services, are selected. Data from electronic service invoices in the referred period were made available by the Secretariat of Finance of Fortaleza and the information provided was applied to econometric models in multivariate analysis to identify the determinants of this flow of intermunicipal services. Following the literature, gravitational models were estimated and the results of the estimates suggest that the flow of trade in services from Fortaleza presents resistance in relation to distance and attraction in relation to the municipality's income. Specifically, they allow us to infer that the services trade in Fortaleza is mainly destined to other Brazilian capitals, which are high-income municipalities, and to its metropolitan region, a fact that proves the relevance of the distance factor.